2017
DOI: 10.1016/j.tcs.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

On Boolean combinations forming piecewise testable languages

Abstract: A regular language is k-piecewise testable (k-PT) if it is a Boolean combination of languages of the form L a 1 a , where a i ∈ Σ and 0 ≤ n ≤ k. Given a finite automaton A , if the language L(A ) is piecewise testable, we want to express it as a Boolean combination of languages of the above form. The idea is as follows. If the language is k-PT, then there exists a congruence ∼ k of finite index such that L(A ) is a finite union of ∼ k -classes. Every such class is characterized by an intersection of languages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…For most levels of the ST hierarchy, it is not even known if this problem is decidable, and when it is, exact complexity bounds are often missing [31]. The main exception are J-trivial languages -level 1 of the hierarchy -which have recently attracted some attention, motivated by applications in algebra and XML databases [17,22,28].…”
Section: Theorem 7 a Regular Language Is R-trivial If And Only If Itmentioning
confidence: 99%
“…For most levels of the ST hierarchy, it is not even known if this problem is decidable, and when it is, exact complexity bounds are often missing [31]. The main exception are J-trivial languages -level 1 of the hierarchy -which have recently attracted some attention, motivated by applications in algebra and XML databases [17,22,28].…”
Section: Theorem 7 a Regular Language Is R-trivial If And Only If Itmentioning
confidence: 99%
“…The construction is illustrated in Table I. The length of W k,n is k+n k −1, and a n appears exactly k times in W k,n [24]. For defining A k,n , it is useful to set W k,n = ε whenever kn = 0.…”
Section: Appendix B Logarithmic Encoding Of a K-step Countermentioning
confidence: 99%
“…[HM15]. Deciding whether a DFA or a NFA A recognises a n-PT language is coNP-complete or PSPACE-complete respectively (see [MT17] and the references therein). The methods underlying these algorithms usually provide a bound on hpLq in terms of A: Klíma and Polák showed that hpLq is bounded by the maximal length of a simple path from an initial to a final state in A [KP13].…”
Section: Introductionmentioning
confidence: 99%